2010
DOI: 10.1186/1471-213x-10-37
|View full text |Cite
|
Sign up to set email alerts
|

The endocytic recycling regulator EHD1 is essential for spermatogenesis and male fertility in mice

Abstract: BackgroundThe C-terminal Eps15 homology domain-containing protein 1 (EHD1) is ubiquitously expressed and regulates the endocytic trafficking and recycling of membrane components and several transmembrane receptors. To elucidate the function of EHD1 in mammalian development, we generated Ehd1-/- mice using a Cre/loxP system.ResultsBoth male and female Ehd1-/- mice survived at sub-Mendelian ratios. A proportion of Ehd1-/- mice were viable and showed smaller size at birth, which continued into adulthood. Ehd1-/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 42 publications
(63 reference statements)
7
85
0
Order By: Relevance
“…Similarly, deficiency of protein interacting with C kinase 1 (PICK1), which is highly expressed in round spermatids and is involved in vesicle trafficking from the Golgi apparatus to the acrosome, causes globozoospermia and infertility in male mice (Xiao et al 2009). Further, Rainey et al (2010) showed that EHD1, a regulator of endocytic recycling/sorting, was essential for normal sperm morphogenesis in mice (Rainey et al 2010). In this study, we identified SAMT1 as a novel, TGN-and MVB-localized protein that may function in vesicle trafficking and/or protein degradation.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, deficiency of protein interacting with C kinase 1 (PICK1), which is highly expressed in round spermatids and is involved in vesicle trafficking from the Golgi apparatus to the acrosome, causes globozoospermia and infertility in male mice (Xiao et al 2009). Further, Rainey et al (2010) showed that EHD1, a regulator of endocytic recycling/sorting, was essential for normal sperm morphogenesis in mice (Rainey et al 2010). In this study, we identified SAMT1 as a novel, TGN-and MVB-localized protein that may function in vesicle trafficking and/or protein degradation.…”
Section: Discussionmentioning
confidence: 75%
“…This proposition is supported by transgenic mouse models demonstrating spermiation failure in younger animals and a progressive decline in other aspects of spermatogenesis (reviewed in ref. 72). …”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Elucidation of the clathrin-mediated endocytosis interactome highlights the complexity of this process and identifies key "hubs", such as the adaptor protein complex AP2 and accessory proteins that regulate endocytotic pathways, for future research attention. 94 The C-terminal Eps15 homology domain-containing (EHD) protein Ehd1 participates in clathrin-mediated endocytosis by regulating the rate of endocytic recycling to the cell surface, 72 but can also participate in the Arf6-mediated pathway for bulk recycling of plasma membrane proteins through non-clathrin-associated of actin dynamics, signal transduction pathways and endocytic pathways involved in trafficking proteins to either recycling or degradative pathways. 12,47,93 An emerging picture of the composition of TBCs, and the endocytic vesicles that arise from these structures (reviewed in ref.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation
“…In light of this work, it will also be interesting to reexamine the functions of mammalian EHD1 and EHD3 using genetic models. Knockout of mouse EHD3 by itself does not impact viability or development in clear ways, and knockout of EHD1 affects spermatogenesis (George et al, 2011;Rainey et al, 2010). Double mutants may be required to uncover clear effects on mammalian ciliogenesis.…”
mentioning
confidence: 99%